MOTIVATION, ANXIETY, AND PLEASURE (FOREIGN LANGUAGE ENJOYMENT) IN LEARNING ENGLISH: INTERACTIONS AND PEDAGOGICAL IMPLICATIONS - Seilkhanova Rita Nurniyazovna; Khojabaeva Gulbanu Erbol qizi (Web of Journals Publishing, 2026)
The article examines three key psychological factors influencing English language success: motivation, anxiety, and pleasure from learning a foreign language (Foreign Language Enjoyment, FLE). Modern approaches to studying the emotional-motivational sphere in English teaching methodology, including self-determination theory, the concept of foreign language anxiety, and positive psychology, are analyzed. Special attention is paid to how FLE can compensate for the negative impact of anxiety and enhance learners' motivation. In conclusion, pedagogical strategies for increasing motivation and FLE and reducing anxiety in English lessons are proposed.
Keywords: Motivation, anxiety, Foreign Language Enjoyment, learning English, emotional factors, positive psychology, EFL.